(untitled) (Journal of the College of Basic Education, 2025)
The research aimed to identify the level of mathematical literacy of mathematics teachers of the third intermediate grade. To achieve this, the researcher used the descriptive approach and the research community consisted of (390) teachers and the research sample consisted of (162) teachers and teachers (85) who served less than 10 years and (77) who served more than ten years were randomly selected. The researcher built the research test, which consisted of a mathematical literacy test consisting of (32) items of the objective type, and its psychometric properties were verified, and the test was applied to the research sample and performed statistical treatments using the (spss) program and the adoption of the (t) test for one sample and two independent samples, and the results showed the following: 1- Mathematics teachers of the third intermediate grade have an acceptable level of mathematical literacy. 2 - The level of mathematical literacy is equal for those who served less than ten years and those who served more than 10 years. In light of the results, the researcher made some relevant recommendations and suggested a number of suggestions that can be utilized in future studies